Politik Hukum dalam Proses Pemindahan Ibu Kota Negara Melalui Pembentukan Undang-Undang Ibu Kota Negara (UU IKN) - Elsa Benia; Ghina Nabilah (Jurnal Hukum Lex Generalis, 2022)
The ratification of Law Number 3 of 2022 concerning the State Capital (UU IKN) has many pros and cons. This is because the formation of the IKN Law has many inconsistencies, such as the lack of public participation and the shortness of the formation process because it only takes 43 days. Then, legal politics has a strong relevance to the policy direction of forming legal products. This paper uses a normative juridical method with a law and case approach. The results of the study stated that in the formation of the IKN Law, the legal politics in it did not reflect the needs of the community. It is evident from the shallow analysis of academic texts to indications of formal and material defects due to hasty formation.